2012
DOI: 10.1007/s10096-012-1613-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prognosis of fulminant viral hepatitis in late pregnancy by the MELD scoring system

Abstract: The purpose of this paper was to analyze the prognosis of women with fulminant viral hepatitis in late pregnancy (FVHILP) by the Model for End-Stage Liver Disease (MELD) scoring system. A retrospective study involving patients admitted to two tertiary hospitals between January 1, 1994 and June 30, 2011 was undertaken. The relations between MELD scores and change of MELD score over time (ΔMELD) and prognosis during hospitalization were analyzed. Among the 54 patients with FVHILP, the MELD scores on admission we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…We identified 6 studies [79][80][81]83,86,87 evaluating 526 ALF patients and, overall, 304 (58%) died. All studies did not have liver transplantation available so this eliminates bias owing to competing outcomes but the samples were not representative of Western populations (causes of ALF and management will be different).…”
Section: Meld Criteriamentioning
confidence: 99%
“…We identified 6 studies [79][80][81]83,86,87 evaluating 526 ALF patients and, overall, 304 (58%) died. All studies did not have liver transplantation available so this eliminates bias owing to competing outcomes but the samples were not representative of Western populations (causes of ALF and management will be different).…”
Section: Meld Criteriamentioning
confidence: 99%
“…In previous studies [1,10] based on 1-way analysis of variance in the prognosis of FVHILP, it was found that Tch, PTA, Scr, WBC, and the presence of 3 or more intractable complications were important factors influencing patient prognosis. The MELD scoring system is also effective at evaluating the prognosis of FVHILP [21]. In the present study, blood test results and the occurrence of major complications showed that pre-delivery maternal conditions were similar between the SVD group and the cesarean group.…”
Section: Discussionmentioning
confidence: 53%
“…In summary, preventive strategies of HBV MTCT have evolved from routine schedules after delivery to medication during pregnancy and delivery. Although the results of many of the trials have not yet been integrated into national or international guidelines, with the development of novel techniques, drugs, and additional large‐scale clinical trials (Figure ), the problem of MTCT of HBV may be minimized, and millions of children of HBV‐carrying mothers will enjoy a better life, free of potential liver disease .…”
Section: Resultsmentioning
confidence: 99%